Perspective—Localized Corrosion: Passive Film Breakdown vs Pit Growth Stability. Issue 4 (24th February 2017) - Frankel, G. S.; Li, Tianshu; Scully, J. R.
Abstract : A debate about the critical step in localized corrosion has raged for decades. Some researchers focus on the composition and structure of the passive film associated with the initial breakdown of the film, whereas others consider that the susceptibility to pitting is controlled by the pit growth kinetics and the stabilization of pit growth. The basis for a unified theory of pitting is presented here in which pit stability considerations are controlling under aggressive conditions (harsh electrolytes and extreme environments and/or susceptible microstructures) and the passive film properties and protectiveness are the critical factors in less extreme environments and/or for less susceptible alloys.